The "responsibility to prevent": an international crimes approach to the prevention of mass atrocities - Reike, R (2014)
Paragraphs 138 to 140 of the Outcome Document of the 2005 UN World Summit not only elevated the element of prevention to a prominent place within the principle of “responsibility to protect” (R2P), but also restricted the scope of R2P to four specific crimes under international law: genocide, war crimes, ethnic cleansing, and crimes against humanity. This thesis explores the conceptual and practical consequences of linking R2P to the concept of international crimes, with a particular focus on the preventive dimension of R2P, the socalled “responsibility to prevent”. To date, much of what has been written about the “responsibility to prevent” borrows primarily from conflict prevention theory and practice. Such conflict prevention inspired accounts of the “responsibility to prevent” tend to depict the principle as a long-term agenda that seeks to build societies resilient to atrocity crimes; that rests primarily on pillars one (state responsibility) and two (international assistance and capacity-building); that is supportive rather than undermining of state sovereignty; and that can largely adhere to the traditional conflict prevention principles of impartiality, consent, and minimal coercion should more direct prevention efforts become necessary. Drawing on literature from criminology, this thesis develops an international crimes framework for operationalizing the preventive dimension of R2P. The framework, combined with three case studies of international crime prevention (Bosnia 1991-1995; Kenya 2007-08; and Libya 2011), challenges key assumptions of the conflict prevention accounts, arguing that linking R2P to the concept of international crimes turns the “responsibility to prevent” into a principle that is more focused on the short-term, rather than on so-called root causes of atrocity crimes; more focused on individuals, rather than on state structures and capacity; more partial regarding perpetrators and victims; and more coercive, intrusive, and controversial than is commonly acknowledged in academic writing and policy debates on the subject. More broadly, the thesis concludes that taking R2P’s focus on the prevention of international crimes seriously requires re-rethinking the “responsibility to prevent” in important respects.